Anti-CD38 antibody therapy for patients with relapsed/refractory multiple myeloma: differential mechanisms of action and recent clinical trial outcomes - Leleu, Xavier; Martin, Thomas; Weisel, Katja; Schjesvold, Fredrik; Iida, Shinsuke; Malavasi, Fabio; Manier, Salomon; Chang-Ki Min; Ocio, Enrique M; Pawlyn, Charlotte; Perrot, Aurore; Quach, Hang; et al. (Annals of hematology, 2022)
CD38 is a transmembrane glycoprotein that functions both as a receptor and an ectoenzyme, playing key roles in the regulation of calcium signaling and migration of immune cells to tumor microenvironments. High expression on multiple myeloma (MM) cells and limited expression on normal cells makes CD38 an ideal target for the treatment of MM patients. Two monoclonal antibodies directed at CD38, isatuximab and daratumumab, are available for use in patients with relapsed and/or refractory MM (RRMM); daratumumab is also approved in newly diagnosed MM and light-chain amyloidosis. Clinical experience has shown that anti-CD38 antibody therapy is transforming treatment of MM owing to its anti-myeloma efficacy and manageable safety profile. Isatuximab and daratumumab possess similarities and differences in their mechanisms of action, likely imparted by their binding to distinct, non-overlapping epitopes on the CD38 molecule. In this review, we present the mechanistic properties of these two antibodies and outline available evidence on their abilities to induce adaptive immune responses and modulate the bone marrow niche in MM. Further, we discuss differences in regulatory labeling between these two agents and analyze recent key clinical trial results, including evidence in patients with underlying renal impairment and other poor prognostic factors. Finally, we describe the limited existing evidence for the use of isatuximab or daratumumab after disease progression on prior anti-CD38 mono- or combination therapy, highlighting the need for additional clinical evaluations to define optimal anti-CD38 antibody therapy selection and sequencing in RRMM.
Keywords: ADP-ribosyl Cyclase 1; klinické zkoušky jako téma; Clinical Trials as Topic; Multiple Myeloma; Tumor Microenvironment; Monoclonal antibody; lidé; nádorové mikroprostředí; Myeloma; CD38; mnohočetný myelom; antigeny CD38; protinádorové látky imunologicky aktivní; Humans; Antineoplastic Agents, Immunological; Therapy